Variabilidade genética, estrutura populacional e filogeografia do mapará (Hypophthalmus marginatus Valenciennes, 1840 - Pimelodidae, Siluriformes) no Estado do Pará, utilizando sequências de DNA mitocondrial - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2012)
The maparás Hypophthalmus spp. have contributed substantially to the fish landings in the Amazon region, although the population-genetic aspects about their is poorly known. Therefore, this study aims to evaluate the genetic variability, population structure and phylogeography of the most commercialized species, H. marginatus, in eight localities in the State of Pará, to provide information supporting sustainable exploitation policies for the species. We obtained 547 bp of the control region of mitochondrial DNA from 241 individuals of H. marginatus. The phylogenetic tree separated the individuals into two monophyletic clades, called Type I and Type II, with high bootstrap values, which suggests its division into two species. This was supported by the high genetic divergence of 8.8% between the types, the network of haplotypes where the haplogroups I and II were separated by 44 mutations, the analysis of molecular variance whereas 83.77% of the variance was attributed to differences between groups, and the fixation index values greater than 0.82 indicating absence of gene flow mediated by females between the two groups. The two types of H. marginatus coexist in the Tapajós and Xingu, and only Type I occurs in the Amazon, Tocantins and Pará River estuary, while only the Type II occurs in the Anapú river. Therefore, studies involving larger samples and other rivers of the Amazon should be performed to define the actual range of each type of H. marginatus. Genetic diversity was high in all populations of Types I and II, suggesting that fishing pressure does not reduce, in the short term, the genetic variability of the species. The analysis of population within the Types I and II suggests the absence of genetic substructuring associated to the tributaries assessed, rejecting the hypothesis of philopatry for H. marginatus and indicating that the migratory ability of these taxa or the flood regime of the Amazonian floodplains may be responsible for the genetic similarity between most populations within groups. Furthermore, the genetic differences observed between populations of the Type I may be the result of random genetic drift or diachronic spawns. For Type I the negative and significant test of neutrality of Fu (Fs) can be associated with the effect of background selection or hitchhiking since population expansion should not be the cause of these results because the indices of genetic diversity and mismatch distribution give evidence of stable populations over evolutionary time. For Type II, the neutrality tests, the genetic diversity and mismatch distribution suggests stable populations over time. Finally, for purposes of management and conservation of Hypophthalmus the present work indicates the presence of at least four species in the Pará state rivers and suggests that studies expanding the collecting area and using nuclear markers are necessary to know the actual diversity of this genus in Amazon.
Keywords: Genética de populações; Região controle; Amazônia; Especiação; CNPQ::CIÊNCIAS EXATAS E DA TERRA; CONSERVAÇÃO E MANEJO DA BIODIVERSIDADE NA AMAZÔNIA